PELAKSANAAN ADAT PRANGKA KAPUNG KABA DALAM PERKAWINAN MASYARAKAT DAYAK MUARA DESA KUALA DUA KABUPATEN SANGGAU - NIM. A1011201318, NUR TASLIMAH (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The customary payment of Pelangkah in marriage among the Dayak Muara community in Kuala Dua Village, Sanggau Regency, is conducted through a ritual procession aimed at honoring ancestral spirits and preventing undesirable events. However, with the passage of time, the “Prangka Kapung Kaba” has undergone changes. The main issue is: